Long-term simulated microgravity alters gut microbiota and metabolome in mice - Yuan, Lu; Zhang, Rong; Li, Xinlou; Gao, Caiyun; Hu, Xiangnan; Hussain, Safdar; Zhang, Linlin; Wang, Moye; Ma, Xiaoyu; Pan, Qiuxia; Lou, Xiaotong; Si, Shaoyan (Frontiers in Microbiology, 2023)
Spaceflight and microgravity has a significant impact on the immune, central nervous, bone and muscle support and cardiovascular systems. However, limited studies are available on the adverse effects of long-term microgravity on the intestinal microbiota，metabolism, and its relationships. In this study, a ground-based simulated microgravity (SMG) mouse model was established to evaluate the impact of long-term microgravity on gut microbiota and metabolome. After eight weeks of SMG, alterations of the intestinal microbiota and metabolites were detected using 16S rRNA sequencing and untargeted metabolomics. Compared to the control, no significant differences in α-diversity were observed at weeks 2, 4 and 8. Nevertheless, there were clear differences in community structures at different time points. The phylum Verrucomicrobia significantly declined from 2 to 8 weeks of SMG, yet the relative abundance of Actinobacteia and Deferribacteres expanded remarkably at weeks 8. SMG decreased the genus of Allobaculum and increased Bacteroides significantly throughout the period of eight weeks. Besides, Genus Akkermansia, Gracilibacter, Prevotella, Odoribacter, Rothia, Sporosarcina, Gracilibacter, Clostridium and Mucispirillum were identified as biomarkers for SMG group. Desulfovibrio_c21_c20, Akkermansia_muciniphila, and Ruminococcus_gnavus dropped at week 2, which tend to recover at week 4, except for Akkermansia_muciniphila. Bacteroides_uniformis and Faecalibacterium_prausnitzii declined significantly, while Ruminococcus_flavefaciens and Mucispirillum_schaedleri elevated at week 8. Furthermore, intestinal metabolome analysis showed that 129 were upregulated and 146 metabolites were downregulated in SMG. Long-term SMG most affected steroid hormone biosynthesis, tryptophan, cysteine, methionine, arginine, proline metabolism, and histidine metabolism. Correlated analysis suggested that the potential beneficial taxa Allobaculum, Akkermansia, and Faecalibacterium were negatively associated with tryptophan, histidine, arginine and proline metabolism, but positively with steroid hormone biosynthesis. Yet Bacteroides, Lachnospiraceae_Clostridium, Rothia, Bilophila and Coprococcus were positively correlated with arginine, proline, tryptophan, and histidine metabolism, while negatively associated with steroid hormone biosynthesis. These results suggest that Long-term SMG altered the community of intestinal microbiota, and then further disturbed intestinal metabolites and metabolic pathways, which have great potential to help understand and provide clues for revealing the mechanisms of long-term SMG involved diseases.